Challenges And Opportunities For Journalistic Communication In The Digital Age: Perspective Of Banjarmasin City, South Kalimantan - Lieta Dwi Novianti; Gina Liliana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
This study aims to investigate the challenges and opportunities faced in journalistic communication in the digital era, with a focus on the city of Banjarmasin, South Kalimantan. The research method involves surveys and interviews with journalists, editors, and digital news media readers. The results of the study show that journalists face significant challenges in maintaining news credibility in the midst of an era of fast and often superficial information on digital platforms. They feel pressure to produce viral content to attract attention, which can potentially compromise the substance of the news. Nonetheless, the opportunities that arise in the digital age are improvements in reaching a wider audience instantly and interacting directly through social media. The conclusion of this study emphasizes the need for collective awareness about the importance of journalistic ethics and the substance of news in digital communication. It requires constant training and education for journalists to develop skills in managing information in the turbulent digital era. While digital challenges are unavoidable, collaboration between editors and journalists can help maintain journalistic integrity. Keywords: journalistic communication , digital era, challenges, opportunities, news credibility, social media, Banjarmasin City.